Studies On The Comparative Effect Of Rosemary Extract And Butylated Hydroxy Anisole On The Keeping Quality Of Value Added Chicken Meat Sausages Chicken Meat Sausages - Reddy, D.Maheswara; Babu, A.Jagadeesh; Rao, B.Eswara; Moorthy, P.R.S.; Gupta, R.S.D. (Journal of Meat Science, 2019)
The present investigation has been designed to know the effect of rosemary extract on the keeping quality of value added chicken meat sausages and to compare the effect of rosemary with synthetic antioxidant i.e. BHA. Significantly (P<0.01) lower values for cooking loss, pH, 2-TBARS and free fatty acid content due to the incorporation of rosemary extract at 0.2 % level during refrigeration storage was observed. Also there was a significant (P<0.01) increase in cooking loss, pH, TBARS values and free fatty acid content as the refrigeration storage period progressed from 0 to 8 days . Microbiological quality evaluation revealed that chicken meat sausages incorporated with rosemary extract at 0.2 % level had significantly (P<0.05) lower standard plate count and coliform count during refrigerated storage as compared to control and other treatment. Organoleptic evaluation indicated that addition of rosemary extract at 0.2% level to chicken meat sausages registered significantly (P<0.01) higher sensory scores for various eating quality attributes than the other treatments.